Video-based learning in EFL contexts: a systematic review of empirical evidence and pedagogical implications - Sylvia, Sylvia (Edumaspul: Jurnal Pendidikan, 2025)
The increasing integration of video-based learning in English as a Foreign Language (EFL) education has transformed the ways learners engage with language, teachers facilitate instruction, and institutions design curricula. This systematic review synthesizes empirical studies published between 2023 and 2025 that examine the pedagogical affordances and challenges of diverse video-mediated approaches, including synchronous video communication, video-enhanced observation, translanguaging in peer editing, video-based shadowing, dubbing applications, and social media integration such as TikTok. Findings reveal that video-based interventions significantly enhance learners’ oral proficiency, pronunciation, reflective practices, cognitive engagement, and socio-emotional involvement. However, their effectiveness is highly contingent upon instructional design, learners’ proficiency levels, technological accessibility, and institutional support. While face-to-face modalities tend to foster richer interactional dynamics and emotional engagement, video-mediated environments provide unique opportunities for reflective practice, multimodal input, and collaborative problem-solving. Challenges such as cognitive overload, reduced social presence, digital distractions, and unequal access underscore the need for pedagogical scaffolding and critical integration. Overall, this review highlights the transformative yet context-sensitive role of video-based learning in EFL education, calling for future research on long-term impacts, differentiated instructional strategies, and the integration of AI-driven adaptive technologies to optimize multimodal learning ecologies.